Reflection of nano-problems in the thesaurus on semiconductor physics - V. N. Beloozerov; N. N. Shaburova (Библиосфера)
The technique, specialized nanotechnology sources and the results of the work in the Institute of Semiconductor Physics and VINITI on development of the information retrieval thesaurus on the physics of semiconductors are discussed. Elements (descriptors) of the thesaurus are the names of the classes of different classification systems: international UDC and PACS, domestic BBK, SRSTI (GRNTI), VINITI Rubricator and specialized nanotechnological classifications. The work was carried out with the aim to add the thesaurus scope and reflect connections between theoretical issues of semiconductor physics and their application in the field of nanotechnology.